1998
DOI: 10.1093/jnci/90.23.1810
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant 5-Fluorouracil and Leucovorin With or Without Interferon Alfa-2a in Colon Carcinoma: National Surgical Adjuvant Breast and Bowel Project Protocol C-05

Abstract: The addition of IFN to 5-FU + LV adjuvant therapy confers no statistically significant benefit, but it does increase toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 9 publications
1
38
0
3
Order By: Relevance
“…Thus, the improved OS hazard ratio for the IFN treatment group in the 5-FU adjusted model could be explained by age or other unobserved nontreatment-related prognostic factors also. These findings confirm the results of other trials that the addition of IFN to 5-FU does not confer a survival benefit (Wolmark et al, 1998). Frequency of grade 3 and 4 toxicities was increased in therapy arms including LEV or IFN.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the improved OS hazard ratio for the IFN treatment group in the 5-FU adjusted model could be explained by age or other unobserved nontreatment-related prognostic factors also. These findings confirm the results of other trials that the addition of IFN to 5-FU does not confer a survival benefit (Wolmark et al, 1998). Frequency of grade 3 and 4 toxicities was increased in therapy arms including LEV or IFN.…”
Section: Discussionsupporting
confidence: 89%
“…The NSABP protocol C-05 evaluated the efficacy of the addition of interferon alfa-2a to 5-FU and leucovorin in the adjuvant treatment of colon cancer. The results of this trial showed no significant difference either in DFS or in OS for the IFN arm (Wolmark et al, 1998). Owing to the absence of significant differences in OS in these trials examining the role of LEV and IFN in the adjuvant setting of colon cancer, continuation of accrual in the present trial was considered as ethically justifiable until the end of the accrual period in 1999.…”
Section: Discussionmentioning
confidence: 78%
“…Two treatment trials and three prevention trials stated that gender subgroup analyses were based on data from previously published reports, and two treatment trials and three prevention trials stated that specific gender hypotheses were being tested. The reports of gender subgroup analyses of treatment outcome showed a higher rate of toxicity among women, 26 higher levels of pretreatment psychological distress among women, 27 a greater proportion of recurrences and treatment failures among women, 28 lower levels of recurrence among women, 29 better response to therapy among women, 30 worse survival among men, 24 and a lower mortality rate among women. 26 One report recommended caution in the interpretation of the subgroup analyses, because the gender analysis was not planned in advance.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, several large-scale studies conducted to demonstrate the efficacy of adjuvant chemotherapy started treatment within 42 days [19][20][21][22]. Only 10 % of all patients with breast cancer in the SEER-Medicare database received chemotherapy 3 months after surgery, and their overall mortality hazard ratio (HR) was 1.…”
Section: Discussionmentioning
confidence: 99%